Is Consumer Buying Influenced By Interested On Packaging Design? - Dika Prayogi; Laras Mei Purbianti; Nanik Kustiningsih; Sri Rahayu; Mochamad Fatchurrohman (LPPPIPublishing, 2022)
This study aims to analyze the effect of design packaging in attracting consumers to buy Crazy Kres’es Product. Kres. Marketing strategies that can be used by companies have different ways, one of which is determining the packaging design. A product marketed with an eye-catching packaging design can attract a consumer's buying interest. Basically, consumers buy a product because they are lulled by the visuals of a product, therefore by paying attention to the visual aspect of packaging design which consists of five indicators, namely color, shape, graphic illustrations and aesthetics, it can attract potential consumers to buy.